Tax crimes and enforcement in the European Union : solutions for law, policy and practice - Turksen, Umut; Vozza, Donato; Kreissl, Reinhard; Rasmouki, Fanou (Oxford : Oxford University Press, 2023)
'Tax Crimes and Enforcement in the European Union' addresses the preventative and prosecution challenges of tax crimes, money laundering, and corruption. The book combines legal and social science methods while analysing law in practice, suggesting future solutions for tax law and policies on enforcement in the EU.
"This is an open access publication, available online and distributed under the terms of a Creative Commons Attribution - Non Commercial - No Derivatives 4.0 International licence (CC BY-NC-ND 4.0)"--Title page verso.
This edition also issued in print: 2023.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 24, 2023).
Keywords: Taxation -- Law and legislation -- European Union countries; Corruption -- Law and legislation -- European Union countries; Tax evasion -- European Union countries; Law; Laws of specific jurisdictions & specific areas of law